It is the lifetime that matters: public preferences over maximising health and reducing inequalities in health. Issue 9 (6th April 2012) - Dolan, Paul; Tsuchiya, Akil
Abstract : Scarce healthcare resources can be allocated in many ways. The National Institute for Health and Clinical Excellence in the UK focuses on the size of the benefit relative to costs, yet we know that there is support among clinicians and the general public for reducing inequalities in health. This paper shows how the UK general public trade-off these sometimes competing objectives, and the data we gather allow us to show the weight given to different population groups, for example, 1 extra year of life in full health to someone who would otherwise die at the age of 60 years is worth more than twice as much as an additional year of life to someone who would otherwise die at the age of 70 years. Such data can help inform the rationing decisions faced by all healthcare systems around the world.